Studi Deskriptif Manajemen Pengetahuan (Knowledge Management) pada Perusahaan Telekomunikasi Multinasional: Studi Kasus pada Perusahaan Ericsson (Jurnal Adabiya, 2020)
Managing knowledge is a crucial aspect for technological industries, such as telecommunication companies. Thecompanies can gain benefit from employee’s knowledge to improve company services as well as to develop advanced products. In fact,managing knowledge is not easy to do considering organization’s cul- ture. The aim of this paper is to analyze the challenges to applyknowledge managementsystem in a multina- tionaltelecommunicationcompany. Thetypeofthisresearchisstudycase.Datawerecollectedbyinterviewing key persons and it was analyzed by using Miles and Huber Man model. The result shows that capturing tacit knowledgeand developing collaborative environment become challenges for Ericsson to manage knowledge. Mostly,staffs preferto keep theirtacitknowledgeratherthantosharethatknowledge.Thisstudyrecommends todevelopcollaborativeenvironmentbybuildingtrustamongstaffsthroughgroupdiscussion.